Inventory management and classification in private medium-sized hospitals in Brazil (Research, Society and Development, 2021)
Background: The rational management of stocks consists of an indispensable tool for a hospital unit to manage in a competitive manner, especially in the case of private networks that are subject to market pressure and of health insurers. Goals: Analyze the consumption of hospital supplies based on classifications that assist strategic processes in hospital management. The study is justified by the lack of parameterization and data input related to the supply items of hospitals managed by a hospital health system in Brazil in terms of centralized information for decision-making by hospital managers. Methods: The study is of an exploratory observational nature and sought the necessary subsidies to improve the relationship between Basic Indicators vs. Hospital in the management of hospital supplies. The perception of health managers and how these researched data can be applied in a structured way in managerial decisions was prioritized. The sample focused on six medium-sized general private supplementary health hospitals, located in six Brazilian states. Results: The ABC Curve that describes the consumption of the products with the highest value used by the hospital, and demonstrated that, in hospital units that have the 30 most used products, most come from a single supplier, which, in an time of urgency, hinders the agility in the replacement. Conclusion: Each manager must direct the stock of their hospital unit according to the classification that best meets the profile of their institution to ensure logistics in stock management.